2012
DOI: 10.1520/acem20120002
|View full text |Cite
|
Sign up to set email alerts
|

Relating Compressive Strength to Heat Release in Mortars

Abstract: Conventionally, isothermal calorimetry and ASTM C186 heat of hydration results are reported on a per mass of cement (powder) basis, with typical units being J/g (cement) for example. Based on the recognition that it is the filling of porosity with hydration products that is chiefly responsible for strength development in cement-based materials, there may be merit in instead reporting these results on a per unit volume of (initial) water basis. This paper examines a database of well over 200 mortar mixtures to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 13 publications
3
58
2
Order By: Relevance
“…Measured concrete compressive strength as a function of the measured cumulative heat release (per unit volume of water) used to establish a strength-heat release linear relationship (dashed line, R 2 =0.91) [20]. Purdue regression line was taken from [21] . Measured net expansion (0 °C to 100 °C) vs. initial length for the two NIST standard reference materials [43,44].…”
Section: List Of Figuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Measured concrete compressive strength as a function of the measured cumulative heat release (per unit volume of water) used to establish a strength-heat release linear relationship (dashed line, R 2 =0.91) [20]. Purdue regression line was taken from [21] . Measured net expansion (0 °C to 100 °C) vs. initial length for the two NIST standard reference materials [43,44].…”
Section: List Of Figuresmentioning
confidence: 99%
“…(per unit volume of water) used to establish a strength-heat release linear relationship (dashed line, R 2 =0.91) [20]. Purdue regression line was taken from [21]. Previous evaluation of the influence of aggregates on concrete properties has been limited to only a few aggregate properties and has never included so many different aggregate mineralogies [2,5,10,12,[22][23][24][25][26][27], as in the current study.…”
Section: Introductionmentioning
confidence: 99%
“…By doing this, and assuming that the volume of created hydration products is proportional to the heat generated, one can potentially relate the space-filling capabilities of the hydration products with strength (Bentz, Barrett, De la Varga, & Weiss, 2012). A slower heat development is observed with increasing fly ash replacement level as the fly ash is less reactive than the cement, though the fly ash can provide additional space between the cement particles and can act as a nucleating agent which both increase the hydration rate of the cement.…”
Section: Influence Of Fly Ash On the Hydration Rate And Strength Devementioning
confidence: 99%
“…Bentz et al [12] experimented on a variety of mortar mixtures demonstrated that the compressive strength and cumulative heat of hydration have a linear relationship. Tanesi and Ardani [13] also indicated that the heat of hydration evaluated by isothermal calorimetry turns out to have good correlation with compressive strength at early ages for FA mortar specimens.…”
mentioning
confidence: 99%
“…Statically a valid correlation between degree of hydration and compressive strength of normal and blended cement FA are equally found by Shafiq [14]. Journal of Materials Science and Chemical Engineering Given that heat production provides a good indication of the strength development [12] [13] [14], it can be used as a tool to predict the strength development of FA based concrete. It should suffice to rely on the w:b ratio of the paste sample to experimentally determine the degree of hydration of concrete.…”
mentioning
confidence: 99%